Islamic State of Iraq and Syria (ISIS) Terrorism Action in Indonesia Between 2014-2018 - Indra Martian Permana; Fadzli Adam (Cyber Media Indonesia, 2020)
The Islamic State of Iraq and Sham (ISIS) was declared in Syria in 2014 and then spread to Indonesia. ISIS in Indonesia then spread the understanding of violence and terrorism so then with that understanding ISIS in Indonesia committed many acts of terrorism against the government and the people of Indonesia. This research aims to find out the cause of the birth of terrorism groups, related to the terrorism movement in Indonesia and the movement of groups affiliated with ISIS in Indonesia from 2014-2018 since ISIS was declared in Syria in 2014, both those who committed acts of terrorism and only supported ISIS. This method of research is Kualitatif the method of providing more directed to descriptive. Qualitative research in this paper research takes two methods, namely document analysis taken from written material and the results of the discussion by making a conversation with various parties who know information related to the ISIS terrorism movement from 2014-2018. ISIS groups in Indonesia carried out acts of terror throughout 2014-2018 as many as 48 acts of terrorism. 22 acts of terror were committed against members and police stations because they were considered as enemies. In addition, the attack was aimed at houses of worship in the form of blasting churches and attacking public places and facilities with an explosion in Thamrin and the Malay bus station. This research serves as material for researchers who examine the terrorism movement of the ISIS group in Indonesia, researchers in the social field who study the ISIS social movement and its impact in Indonesia as well as researchers in the field of Islamic studies and Islamic thought which examines various kinds of Islamic thought. This research reveals new facts related to the ISIS organization in Indonesia, the ISIS organization movement in Indonesia and the acts of terrorism committed. changes in terrorist organizations and new patterns related to terrorist attacks and targets by ISIS Indonesia. DOI: https://doi.org/10.5281/zenodo.4032974